Relationships of Hyperhomocysteinemia and Hyperuricemia With Metabolic Syndrome and Renal Function in Chinese Centenarians - Fu, Shihui; Yao, Yao; Zhao, Yali; Luan, Fuxin (Frontiers in Endocrinology, 2018)
As the first time worldwide, this study aimed to investigate the relationships of hyperhomocysteinemia and hyperuricemia with metabolic syndrome (MetS) and renal function in Chinese centenarians. China Hainan Centenarian Cohort Study was performed in 18 cities and counties of Hainan Province. Home interview, physical examination and blood analysis were performed in 808 centenarians following standard procedures. All centenarians had a median age of 102 (100-115) years. Prevalence of hyperhomocysteinemia and hyperuricemia was 91.6% (740 centenarians) and 28.5% (230 centenarians), respectively. MetS was presented in 117 centenarians (14.5%). In simple correlation analyses, hyperhomocysteinemia and hyperuricemia were significantly correlated with MetS and glomerular filtration rate (GFR)<60 ml/min/1.73 m2 (P<0.05 for all). Serum homocysteine levels were significantly correlated with GFR, waist circumstance (WC) and triglyceride levels, while serum uric acid levels were significantly correlated with these variables plus high-density lipoprotein cholesterol (HDL-C) levels (P<0.05 for all). In Logistic regression analyses, hyperhomocysteinemia and hyperuricemia were significantly associated with MetS and GFR<60 ml/min/1.73 m2 (P<0.05 for all). In linear regression analyses, serum homocysteine levels were significantly associated with GFR, WC and triglyceride, while serum uric acid levels were significantly associated with these variables plus HDL-C (P<0.05 for all). Both hyperhomocysteinemia and hyperuricemia had important relationships with MetS and renal function in Chinese centenarians. Hyperuricemia and hyperhomocysteinemia that could help identify and affect the development of MetS and renal function may provide effective prevention strategies and unfold complex relationship between MetS, renal function and cardiovascular risk.